Visual Da'wah Messages: The Creativity of Islamic Content on TikTok and Instagram - Kapsan Usman Utomo Nasution (Department of Islamic Communication and Broadcasting - Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2024)
This study explores the role of visual Islamic content on TikTok and Instagram platforms as an effective medium for modern da'wah (Islamic propagation) among the younger generation. Using a qualitative approach, the research analyzes popular themes, communication strategies, visual creativity, and the impact of visual Islamic content on the audience's religious understanding and practices. The findings reveal that visual Islamic content, featuring themes such as daily Islamic life, practical worship tips, and motivational messages, successfully captures attention and stimulates active engagement through relatable visual creativity and narratives. Content creators, as Islamic influencers, face challenges such as the risk of misinterpretation and the pressure to produce viral content, yet they manage to create a positive impact in shaping a moderate, friendly, and inclusive image of Islam. This content also plays a significant role in countering negative stereotypes and promoting values of tolerance and diversity. The study concludes that visual Islamic content not only serves as an effective tool for da'wah but also as a means to build harmonious digital communities and improve the image of Islam in the digital era